The Effect of E-Services Quality and Security on Customer Satisfaction and Loyalty in Small and Medium-Sized Hotels - Ali Morshed Alsardia; Albattat Ahmad; Norhidayah Azman (Research Parks Publishers, 2024)
The hotel industry is critical to Jordan's economy, particularly small and medium-sized enterprises that provide affordable and convenient lodging for visitors and business travellers Hotels often lack the financial capacity to invest in technology comparable to that of larger establishments, resulting in a disparity between client expectations and actual service provision. This disparity may result in customer unhappiness and a diminished probability of repeat patronage, endangering the long-term viability of these enterprises. Consequently, investigating the influence of e-service quality on fostering client loyalty via satisfaction in small and medium-sized enterprises (SMHs) is essential for comprehending how small organizations can effectively utilize constrained resources to fulfill and surpass consumer expectations. This study seeks to address significant research deficiencies in the SMH sector. This heightened satisfaction affects subsequent behaviors, including the likelihood of repurchase and total consumer allegiance. When performance fails to meet expectations, dissatisfaction emerges, often resulting in negative word-of-mouth or a decrease in repurchase intentions. Expectation-Confirmation Theory offers a robust paradigm for examining the correlation between e-service quality and client loyalty, mediated by customer satisfaction. The application of Jordanian SMHs offers a robust theoretical basis for examining the correlation between digital service quality and customer loyalty. This study aims to address a significant vacuum in the literature by applying ECT to this particular sector, providing valuable insights for both scholars and practitioners in the hotel industry. The results will furnish explicit recommendations for SMHs to enhance their digital services, elevate client pleasure, and ultimately foster greater customer loyalty in a fiercely competitive sector.